2021
DOI: 10.3390/ma14216667
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Solid-State Processes and Heat Treatment on the Properties of AA7075 Aluminum Waste Recycling Nanocomposite

Abstract: Direct solid-states, such as hot extrusion and equal channel angular pressing (ECAP), are alternative and efficient solid-state processes for use in recycling aluminium scrap. These processes utilise less energy and are eco-friendly. Ceramic particles such as ZrO2 are suggested as alternatives in the production of metal composites. This study investigated and optimised the effects of various parameters of reinforced ZrO2 nanoparticles on the mechanical and physical properties via response surface methodology (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Sabbar et al applied the central composite design (CCD) for solid-state recycling of AA7075 chips reinforced by zirconium dioxide (ZrO 2 ) nanoparticles by direct extrusion and ECAP, then followed by heat treatment.The extrusion ratio and temperature were 5.4 and 300⁰C, respectively.The factorial design parameters were ZrO 2 volume fraction (VF% = 1, 3, and 5), heat treatment temperature (T = 450, 500, 550 ⁰C), and heat treatment time (t = 1, 2, and 3 hours). The results showed that the optimum density, hardness, and tensile strength were obtained at VF% = 1, T = 550⁰C, and t = 1.58 hours [12] .…”
Section: Introductionmentioning
confidence: 95%
“…Sabbar et al applied the central composite design (CCD) for solid-state recycling of AA7075 chips reinforced by zirconium dioxide (ZrO 2 ) nanoparticles by direct extrusion and ECAP, then followed by heat treatment.The extrusion ratio and temperature were 5.4 and 300⁰C, respectively.The factorial design parameters were ZrO 2 volume fraction (VF% = 1, 3, and 5), heat treatment temperature (T = 450, 500, 550 ⁰C), and heat treatment time (t = 1, 2, and 3 hours). The results showed that the optimum density, hardness, and tensile strength were obtained at VF% = 1, T = 550⁰C, and t = 1.58 hours [12] .…”
Section: Introductionmentioning
confidence: 95%
“…Nanocomposites often possess improved tensile properties but poor work-hardening ability due to the significant refinement of matrix grain sizes [ 4 , 7 ]. Among the material processing methods, powder metallurgy (PM) has shown great advantages in dispersing nano-reinforcements uniformly and achieving good properties [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%